Impact of COVID-19 pandemic and the lockdown on invasive meningococcal disease - Muhamed-Kheir Taha; Ala-Eddine Deghmane (BMC Research Notes, 2020)
Abstract Objective Few data are available on the association between SARS-CoV-2 and secondary bacterial infections. Such an association was described for flu and invasive meningococcal disease (IMD). We aimed exploring such a correlation between COVID-19 and IMD as well as the impact of the lockdown on IMD. Results We compared IMD cases received at the French National Reference Centre for meningococci and Haemophilus influenzae that are sent as part of the mandatory reporting of IMD. We compared these data during the period 01 January-15 May 2020 to those from the same period in 2018 and 2019. IMD cases that were associated with respiratory presentations significantly increased in 2020 compared to 2018 (P = 0.029) and 2019 (P = 0.002), involved elderly and were due to unusual isolates. However, IMD cases due to hyperinvasive isolates decreased during the lockdown. Enhancing IMD surveillance and anti-meningococcal vaccination in elderly should be addressed.